Effect of Biofertilizers on Benefit & Cost Ratio of Dragon fruit - Prabhat Kumar; Jagveer Singh; Avdhesh Kumar; Divyansh Mishra; Vedant Singh (The Bioscan, 2025)
The present investigation entitled “Studies on natural farming in Dragon Fruit [Hylocereus costaricensis (Web.) Britton and Rose]” was carried out during the year 2023-24 and 2024-25 at Main Experiment Station, Department of Fruit Science, College of Horticulture and Forestry, ANDUAT, Kumarganj, Ayodhya, Uttar Pradesh, India. The treatments comprised of the spraying of different biofertilizers (FYM, Vermicompost, Panchgavya, Amritpani and Jeevamrit) to study benefit and cost ratio of dragon fruit. The experiment was conducted in randomized block design (RBD) with Seven treatments and three replications. The experiment consisted of seven treatments treatments (T1- Control, T2- FYM + Panchgavya, T3- FYM + Amritpani, T4- FYM + Jeevaamrit, T5- Vermicompost + Panchgavya, T6- Vermicompost + Amritpani and T7- Vermicompost + Jeevaamrit) were used for this study. The highest benefit and cost ratio found in treatment T5- Vermicompost + Panchgavya and lowest observed in T1.